Sebuah pengujian terhadap hubungan kausalitas antara belanja pemerintah dan pendapatan pemerintah: Sebuah analisis kointegrasi - George Hondroyiannis; Evangelia Papapetrou (Economic Journal of Emerging Markets, 1999)
This paper test the validity of the proposition that there is a causal relationship between government expenditure and government reveneu for Greece over the period 1957-1993. The empirical analysis employs tests of cointegration as pre-test for Granger test of causality. The empirical evidence suggest that there is a long run relationship between expenditure and revenue  and ecpenditures cause revenue.